Prevalence of Helicobacter pylori in children 2-16 years with chronic Idiopathic thrombocytopenic purpura referred to hematology clinic of Ardabil during 2013-2015 - Vafaie, Majid; Fathi, Afshin; Modarres, Ania (International Journal of Advances in Medicine, 2017)
Background: Idiopathic thrombocytopenic purpura (ITP) is the most common autoimmune blood disorder which leads to premature destruction of platelets by producing antibodies using phagocytic cells against antigens of platelets surface especially in the spleen. Recently, several studies have reported the high prevalence of H. pylori infection in adult patients with chronic ITP, but the studies performed in this area have been very limited in children. The purpose of this study is to investigate the prevalence of Helicobacter pylori infection in children with chronic ITP. Methods: In this case- control study, the case sample includes 30 children in the age range of 2-16 years with chronic ITP and control samples includes 90 children in the age range of 2-16 years who are healthy in terms of ITP disease. A questionnaire and a stool sample is prepared for each sample. These samples are examined by the method of ELIZA kit for the presence or absence of antigen H. Pylori. Data analyzed by statistical methods in SPSS.19. Results: Of the total 30 children with chronic ITP who has referred to the haematology ward of the hospital, H.pylori + 16.7%, we had H.pylori + 20% from a total of 90 controls (P=0.68). The average age of the case and control groups were 6.9±2.8 and 6.9±3 years, respectively; there is no a direct relationship between helicobacter pylori infection and sex, drinking water, but there is a statistically significant difference between platelet levels and the prevalence of H Pylori in the case group (p<0.05); however, this difference is not significant in the control group. Conclusions According to a conducted study, Helicobacter pylori infection is not considered as a factor risk in the development of chronic thrombocytopenic purpura in children. So, it is recommended that further studies to be done in different ethnic groups in the world with more samples, especially in the age range of children, so that the role of Helicobacter pylori in the pathogenesis of chronic autoimmune thrombocytopenic purpura can be determined accurately.